How Do Voters Perceive Disabled Candidates? - Reher, Stefanie (Frontiers in Political Science, 2021)
In order to form an impression of the traits, views, and competences of election candidates, voters often draw on existing stereotypes about their identities and characteristics, such as their gender or ethnicity. Meanwhile, although there is strong stigma associated with disability in our societies, we know very little about how voters perceive candidates with disabilities. This study uses a survey experiment with a conjoint design conducted in Britain to examine the effects of candidate disability on voter perceptions of their personality traits, beliefs, and issue competences. Contrary to common stereotypes, physically disabled candidates are not seen as incompetent and weak. Instead, they are perceived as more compassionate, honest, and hard-working than non-disabled candidates, although the effects are modest in size. They are also assumed to be further to the left ideologically and more concerned about and competent in dealing with policy on healthcare, minority rights, and social welfare. The study enriches our understanding of the role of disability in electoral behaviour and political representation while also providing valuable – and overall encouraging – insights for disabled (aspiring) politicians and political parties.